Pengaruh Biaya Operasional Pendapatan Operasional (BOPO) dan Non-Performing Loan (NPL) Terhadap Return on Assets (ROA) pada Perbankan Badan Usaha Milik Negara (BUMN) yang Terdaftar di Bursa Efek Indonesia Periode 2016-2023 - Binasthika, Tata; Sari, Yunita; Herlina, Tati (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to determine the effect of BOPO and NPL on ROA in state-owned banking listed on the Indonesia Stock Exchange (BEI) during the 2016-2023 period. The method used in this research is a quantitative method and panel data regression analysis using the Eviews tool. The data used is secondary data obtained from the annual financial reports of state-owned banks listed on the Indonesia Stock Exchange (BEI) during the 2016-2023 period. The research results show that simultaneously, BOPO and NPL have a significant effect on ROA in State-Owned Enterprise (BUMN) Banking Listed on the Indonesia Stock Exchange for the 2016-2023 period, but partially BOPO has a negative and significant effect on ROA, while NPL has no significant effect on ROA in State-Owned Enterprise (BUMN) Banking Listed on the Indonesia Stock Exchange for the 2016-2023 Period.